Accelerating Flow of Carbon Nanotubes with Carboxymethyl Cellulose and Blood Base Materials with Comparative Thermal Features: Prabhakar Fractional Model. (14th January 2023) - Raza, Ali; Al-Khaled, Kamel; Muhammad, Taseer; Khan, Sami Ullah
Abstract : A fractional model is developed to investigate the thermal onset of carbon nanotubes containing single-wall carbon nanotubes (SWCNTs) and multiwall carbon nanotubes (MWCNTs). The blood and carboxymethyl cellulose (CMC) are utilized to report the characteristics of the base material. The thermal phenomenon is further supported with inclined magnetic force and mixed convection features. The vertical plate with an oscillatory nature induced the flow. After formulating the problem in view of flow assumptions, the fractional framework is carried out via the Prabhakar technique. The validation of the fractional model is ensured in view of previous studies. The comparative thermal aspect of carbon nanotubes and base materials by varying flow parameters is tested.